2020
DOI: 10.1096/fj.201900076rrrrr
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA H19 acts as a miR‐29b sponge to promote wound healing in diabetic foot ulcer

Abstract: Aberrant expression of long noncoding RNA (lncRNA) H19 and microRNA (miR)-29b has been implicated in the complications of diabetes mellitus (DM). As a common and important complication of DM, diabetic foot ulcer (DFU) is characterized by high incidence and poor prognosis. Herein, we explored the role of lncRNA H19 in wound healing of DFU. Differentially expressed DM-related lncRNAs were initially screened by microarray data analysis. DFU models were then induced in DM mouse models. The functional role and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 51 publications
0
44
0
Order By: Relevance
“…Moreover, ectopic overexpression of lncRNA H19 in DFU fibroblasts reduced miR-29b level, resulting in upregulation of FBN1 (Fibrillin 1). 31 These data support therapeutic application of MSC-derived exosomes carrying lncRNA H19 for improved diabetic fibroblast function. 30 A study by Hu et al 32 showed that lncRNA URIDS (Upregulated in Diabetic Skin) is highly expressed in diabetic skin and upregulated in dermal fibroblasts treated with advanced glycation end products (AGE).…”
Section: Long Non-coding Rnas In Wound Healingmentioning
confidence: 64%
“…Moreover, ectopic overexpression of lncRNA H19 in DFU fibroblasts reduced miR-29b level, resulting in upregulation of FBN1 (Fibrillin 1). 31 These data support therapeutic application of MSC-derived exosomes carrying lncRNA H19 for improved diabetic fibroblast function. 30 A study by Hu et al 32 showed that lncRNA URIDS (Upregulated in Diabetic Skin) is highly expressed in diabetic skin and upregulated in dermal fibroblasts treated with advanced glycation end products (AGE).…”
Section: Long Non-coding Rnas In Wound Healingmentioning
confidence: 64%
“…Li et al detected that the expression of H19 and Fibrillin 1 (FBN1) was higher and the expression of miR-29b was lower in the wound tissues of DFU patients. 103 FBN1 is a major component of microfibrils in the ECM and is one of the target genes of miR-29b. 104 They demonstrated that the proliferation and migration of fibroblasts extracted from DFU patients were promoted, while the apoptosis of the cell line was suppressed, when H19 and FBN1 were overexpressed and miR-29b was silenced.…”
Section: Remodeling Stagementioning
confidence: 99%
“…CM is a rich source of extracellular vesicles that encompass a variety of molecular agents, nucleic acids, and proteins. In vitro, R28 retinal cells under stress from oxygen-glucose deprivation (OGD) exposed to MSC-derived EVs significantly minimized the rate of apoptosis and rescued cells from OGD stress [ 91 ]. In support of this, endocytosis of EVs, when delivered into the vitreous cavity, significantly reduced the levels of caspase-3 proteins in the retinal ischemia model [ 91 ].…”
Section: Ischemic Retinal Diseasesmentioning
confidence: 99%
“…In vitro, R28 retinal cells under stress from oxygen-glucose deprivation (OGD) exposed to MSC-derived EVs significantly minimized the rate of apoptosis and rescued cells from OGD stress [ 91 ]. In support of this, endocytosis of EVs, when delivered into the vitreous cavity, significantly reduced the levels of caspase-3 proteins in the retinal ischemia model [ 91 ]. Since a variety of miRNAs are found in EVs isolated from MSCs, few studies have explored the association of miRNA in exosomes in retinal ischemia.…”
Section: Ischemic Retinal Diseasesmentioning
confidence: 99%